Evaluation of Blood Cell Attachment on Er:Yag Laser Applied Root Surface Using Scanning Electron Microscopy - (:unkn) unknown (IVYSPRING INT PUBL, 2013)
Background: Periodontal regeneration is dependent on the uninterrupted adhesion, maturation and absorption of fibrin clots to a periodontally compromised root surface. The modification of the root surface with different agents has been used for better fibrin clot formation and blood cell attachment. It is known that Er:YAG laser application on dentin removes the smear layer succesfully. Aim: The aim of this study is to observe blood cell attachment and fibrin network formation following ER: YAG laser irradiation on periodontally compromised root surfaces in comparison to chemical root conditioning techniques in vitro. Materials and methods: 40 dentin blocks prepared from freshly extracted periodontally compromised hopeless teeth. Specimens were divided in 5 groups; those applied with PBS, EDTA, Citric acid and Er: YAG. They were further divided into two groups: those which had received these applications, and the control group. The specimens were evaluated with scanning electron microscope and micrographs were taken. Smear layer and blood cell attachment scoring was performed. Results: In the Er: YAG laser applied group, smear layer were totally removed. In the blood applied specimens, better fibrin clot formation and blood cell attachment were observed in the Er: YAG group. In the group that had been applied with citric acid, the smear layer was also removed. The smear layer could not be fully removed in the EDTA group. Conclusion: Er: YAG laser application on the root dentin seems to form a suitable surface for fibrin clot formation and blood cell attachment. Further clinical studies to support these results are necessitated.
Keywords: Periodontal regeneration; In vitro; Erbium yag laser; Scanning electron microscopy; ER-YAG LASER; HUMAN GINGIVAL FIBROBLASTS; EARLY HEALING EVENTS; CITRIC-ACID; TETRACYCLINE-HYDROCHLORIDE; PERIODONTAL REPAIR; CEMENTUM; ADHESION; REMOVAL; DOGS